Comparison of Needs, Pressures, and Aspirations among Motherless and Normal Adolescents: A Quantitative-Qualitative Analysis - Shahamat Nia, Mahshid; Arman , Sorour (KMAN Counseling & Psychology Nexus, 2023)
The aim of the present research was to compare needs, pressures, and aspirations among motherless adolescents and their normal counterparts. The research method was of a causal-comparative type and studied the variables using both quantitative (needs and pressures) and qualitative (aspirations) approaches. The statistical population included both male and female adolescents, with and without mothers, in the city of Isfahan. The sample consisted of 60 adolescents (30 motherless and 30 normal), where normal adolescents were selected to match the motherless group. The research tools included a researcher-made scale for assessing adolescent needs and pressures, based on Murray's (1943) theory and the TAT test, and a semi-structured interview for the qualitative part. Quantitative data for needs and pressures were analyzed descriptively (mean and standard deviation) and inferentially (analysis of variance), while qualitative data were examined for aspirations using thematic analysis. The results showed significant differences in needs and pressures between the two groups, except for (need for harm avoidance - pressure of harm and risk). Additionally, thematic analysis of aspirations revealed that aspirations were categorized into 12 themes for motherless adolescents and 6 themes for normal adolescents. Based on these results, it can be said that the absence of a mother in adolescents leads to significant differences in needs and pressures, as well as in the categorization of aspirations. Therefore, practical and applicable training for family members by experienced psychologists and counselors seems essential to prevent crises in families with motherless adolescents.